2006
DOI: 10.1016/j.tet.2005.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of lamellarins D, L, and N

Abstract: Abstract-Total synthesis of cytotoxic marine alkaloids, lamellarins D, L, and N, has been achieved by using Hinsberg-type pyrrole synthesis and palladium-catalyzed Suzuki-Miyaura coupling of the 3,4-dihydroxypyrrole bistriflate 6 as the key reactions.The total yields of lamellarins D, L, and N from the common intermediate 6 are 54, 58, and 50%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 39 publications
2
64
0
Order By: Relevance
“…Iwao et al also reported the synthesis of 36, 37, and 40 in 19%, 18%, and 16% yields over 11, 12, and 12 steps, respectively. They started from isopropyl-protected isovanillin and applied a nitroaldol condensation, a N-dialkylation and Hinsberg pyrrole cyclization reactions (Scheme 8b) [110].…”
Section: Lamellarins and Derivativesmentioning
confidence: 99%
“…Iwao et al also reported the synthesis of 36, 37, and 40 in 19%, 18%, and 16% yields over 11, 12, and 12 steps, respectively. They started from isopropyl-protected isovanillin and applied a nitroaldol condensation, a N-dialkylation and Hinsberg pyrrole cyclization reactions (Scheme 8b) [110].…”
Section: Lamellarins and Derivativesmentioning
confidence: 99%
“…We chose these two highly polar solvents as it is known that polar solvents drive the bromination reaction through the stabilization of bromocyclohexadienone-type intermediates. [17] DMF [18] as well as MeCN [15] have been described previously as good solvents for nuclear bromination reactions of aromatic systems with NBS. However, the bromination of a polyphenol with NBS in THF has only been reported once, [19] and has only rarely been used for the bromination of monosubstituted methoxy-or benzyloxyanilines.…”
Section: Resultsmentioning
confidence: 99%
“…[56][57][58] For example, the total synthesis of lamellarins L (26) and N (105) is shown in Scheme 16. Intermediate (110) was prepared by convergent assembly of bistriflate (106) and arylboronic acids (107) and (108) in a similar manner as described above.…”
Section: -2-2 Synthesis By Iwao (I)mentioning
confidence: 99%